Tecnicas moleculares para evaluar y mejorar el germoplasma vegetal - Ramírez, H.; Calderón, A.; Roca, W. (International Center for Tropical Agriculture, 1991)
Several important aspects of the use of molecular markers in cassava germplasm characterization and in plant breeding programs are indicated. Basic concepts considered include protein and DNA electrophoresis. In the case of cassava, isoenzyme electrophoresis was applied to confirm duplicates detected in CIAT`s cassava collection through morphological characteristics and thus identify new duplicates. In initial evaluations, the isoenzyme alpha-beta- esterase was used and 16 bands were identified in 100 cassava clones; these same bands have been identified in 1200 cassava clones assessed to date. Therefore 2 individuals may possibly be duplicates when they have the same morphological or physiological characteristics and the same electrophoretic pattern of the isoenzyme alpha-beta-esterase. These data should be confirmed with new electrophoretic markers or by direct genome evaluation using the RFLP technique. Indications are given on how to determine the relative electrophoretic mobility (REM) of each band within a zymogram; the duplicity of 2 individuals can then be determined. Band intensity gives an idea of the concn. and catalytic activity of the enzyme in crude tissue extract, but again other markers or RFLP should be used to confirm results. The applications and advantages of RFLPs are analyzed as well as the use of genetic maps and the analysis of multigenic characteristics. (CIAT)